Combination of mean platelet volume and the GRACE risk score better predicts future cardiovascular events in patients with acute coronary syndrome. (September 2014) - Wan, Zhao-Fei; Zhou, Dong; Xue, Jia-Hong; Wu, Yan; Wang, Huan; Zhao, Yan; Zhu, Ling; Yuan, Zu-Yi
Abstract Both the Global Registry of Acute Coronary Events (GRACE) risk score and mean platelet volume (MPV) can independently predict adverse cardiovascular disease (CVD) events in patients with acute coronary syndrome (ACS). This study was aimed at investigating whether MPV was related to the GRACE risk score and whether the combination of them could have a better performance in predicting CVD in Patients with ACS. Totally 297 ACS patients were included. MPV was measured on admission. The GRACE risk score was calculated and its predictive value alone and together with MPV was assessed, respectively. During a median period of 52 months (range, 6 to 65), 11 of the 297 subjects (3.7%) were lost to follow-up, and 132 (46.2%) had adverse CVD including 32 deaths. Both MPV and the GRACE score were higher in patients with CVD events than those without events, and the GRACE score increased with the increase of MPV. Multivariate Cox analysis demonstrated that both MPV and the GRACE score were significant and independent predictors for CVD events (HR: 1.13; 95% CI: 1.10 to 1.15; p = 0.006; HR: 1.30; 95% CI: 1.24 to 1.37; p < 0.001; respectively). The area under the ROC curve was 0.70 (95% CI: 0.64 to 0.76, p < 0.001) when the GRACE score was calculated alone, whereas it increased to 0.85 (95% CI: 0.81 to 0.90, p < 0.001) with the addition of MPV, indicating that the combination of MPV with the scoring system improved the predictive value. This study demonstrates for the first time that MPV is positively associated with the GRACE risk score and it may complement the scoring system in predicting CVD events in patients with ACS.